Interdisciplinary teams for assessing the performance of irrigated agriculture systems - Clemmens, A. J., author; Levine, D. B., author; Dedrick, A. R., author; Clyma, W., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
The Management Improvement Program (MIP) provides a comprehensive methodology for supporting improvement in the profitability and sustainability of irrigated agriculture. Diagnostic Analysis (DA), the MIP's first phase, relies heavily on an interdisciplinary team to assess the performance of irrigated agriculture and provide the foundation for subsequent performance improvements. Small group processes are used to build an effective interdisciplinary team and to frame and concur on understandings that integrate the various disciplinary perspectives. This process compels individuals with diverse technical backgrounds to acquire a holistic understanding of an irrigated agriculture system: farm and district economics, on-farm cultural practices, and water management from source to farm gate to field. structured, periodic professional facilitation is necessary to build and maintain an effective DA Team. Facilitation also helps to assure that all team members actively engage in developing accurate, complete findings that represent the current performance of irrigated agriculture in the study area. Further, stakeholders must be able to understand the DA Team's description of current performance, so they can identify, plan, and carry out needed improvements. A case study is described in which the DA results were received positively and are being used successfully in the subsequent Management Planning Phase.
Irrigation and water resources in the 1990's
Teams for performance assessment
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.